Overview of Program Policy Implementation Village-Based Neighborhood-Owned Enterprises (BUMRT) - Asnar, Asnar (Interdisciplinary Social Studies, 2022)
Background: National development aims to build independence including development, including the neighborhood. One of the government's current missions is to build the area to the bottom level, namely neighborhood, achieved through community empowerment to create a more productive society with business diversity, availability of facilities to support the economy, and optimize the potential that exists for economic growth. Aim: This study aims to determine the Implementation of the Village-Based Neighborhood-Owned Enterprise (BUMRT) Policy in Sidomulyo Village, Samarinda Ilir District, Samarinda City, along with its supporting and inhibiting factors. Method: It is a qualitative research. Purposive and accidental samplings were used. Data were collected through in-depth interviews, role-playing observations, and documentation. For the analysis, it used Miles and Huberman's interactive model data analysis technique. Findings: The human resources available at BUMRT only consist of 6 members. At the planning stage, the village government prepares the budget needs of BUMRT based on the budget proposal submitted by BUMRT. At the budgeting stage, the village government budgets need to be distributed to Community Groups (Pokmas), and then Pokmas distribute budgets related to BUMRT needs. At the evaluation stage, reporting and accountability of the use of funds by BUMRT are carried out. There are activities such as socialization to the community, formation of preparatory teams, proposed draft BUMRT regulations, business license making, employee training, and capital facilitation and assistance, as well as the existence of BUMRT. They are expected to improve the welfare of the community, especially economically, as well as reducing unemployment.